Modified Dual-Band Stacked Circularly Polarized Microstrip Antenna - Guo Liu; Liang Xu; Yi Wang (International Journal of Antennas and Propagation)
A novel high-performance circularly polarized (CP) antenna is proposed in this paper. Two separate antennas featuring the global positioning system (GPS) dual-band operation (1.575 GHz and 1.227 GHz for L1 band and L2 band, resp.) are integrated with good isolation. To enhance the gain at low angle, a new structure of patch and two parasitic metal elements are introduced. With the optimized design, good axial ratio and near-hemispherical radiation pattern are obtained.